Foreword - Caffarelli, Carlo; Calvani, Mauro; Cardinale, Fabio; Chiappini, Elena; Ciprandi, Giorgio; Cravidi, Claudio; Duse, Marzia; Galli, Elena; Licari, Amelia; Manti, Sara; Martelli, Alberto; Minasi, Domenico; et al. (Acta Biomedica Atenei Parmensis, 2020)
The management of chronic diseases are paramount in health care in these days. Among them, there has been an expansion of allergic and immunologic diseases, especially in children. Thanks to the action of the Italian Society of Pediatric Allergy and Immunology (SIAIP), the quality level of care has progressively grown. SIAIP developed a task force with the purpose of proposing updated models for assessing, and prescribing treatment in the allergy and immunology field that have been issued in this supplement. In a very difficult time for everyone, current developments covering a broad range of topics in the field are presented. All Authors have to be thanked, since they have participated with passion and have taken valuable time away from their professional and private interests. We hope that the readership will enjoy these papers.